Can we please have that the right way round? a guide to slide presentations - Robinson, Peter; Cleese, John, 1939-; Norden, Denis; Cossins, James; Jay, Antony, 1930-; Zelazny, Gene (FIRST Training (distributor), 1976)
Contains the basic rules of slide presentation and operation in a form designed to stop anyone who sees it from ever making the classic mistakes again.